Implementasi Delivery Force Automation (DFA) terhadap Kinerja Gudang di PT. Panca Pilar Tangguh Aceh - Adil Ihsan; Imilda; Rita Zahra (Jurnal Manajemen Sistem Informasi (JMASIF), 2025)
This study aims to evaluate the implementation of Delivery Force Automation (DFA) in improving warehouse performance at PT. Panca Pilar Tangguh Aceh. DFA is an automation solution designed to optimize warehouse management and goods distribution, with the goal of enhancing operational efficiency and accuracy in processes such as picking, packing, and shipping. As market demand increases, the company faces challenges in reducing human error and speeding up delivery times. This research uses a descriptive qualitative approach with in-depth analysis through observation, interviews, and literature review. The results indicate that the implementation of DFA successfully improved warehouse operational efficiency, reduced human errors, sped up deliveries, and lowered operational costs. Furthermore, the system contributed to better and more accurate stock management, which positively impacted customer satisfaction and the company’s competitiveness. These findings provide practical guidance for companies in leveraging automation technology to address operational challenges and enhance overall performance.